Incorporação do nexo energia-água em um modelo de otimização da expansão do sistema energético brasileiro - Arroyo, Eveline María Vásquez. (2018)
Often, the decision about the use of a specific technology for energy production and its expansion does not consider important aspects such as water availability and withdrawals from non-energy users. This thesis analyzes the use of water in the energy supply expansion in Brazil. The integrated optimization model MESSAGE-Brazil is used to explore possible impacts on the Brazilian energy system under restriction in the water resources use. Thus, the incorporation of a new water tool is proposed. One of the main challenges faced was the compatibility of the spatial scale of water (hydrographic regions) and energy (energy regionalization) systems. Results of proposed scenarios show the tradeoffs and synergies in the water-energy nexus, in addition to considering a mitigation of greenhouse gas emissions scenario. One of the relevant results of the proposed scenarios is that water cost management system contributes more to a reduction of water withdrawal than the water-rights system. The addition of a water cost to the integrated energy system induces the choice of technologies with a minimal total cost and / or the option for processes that have less water intensive use. This leads to changes in the energy expansion mix of the system and a reallocation of technologies to other hydrographic areas. This thesis therefore reflects the importance of considering the water-energy nexus in the modeling of integrated energy planning with the management of water resources.